(n − 1, n)-weakly prime submodules in direct product of modules - M. Ebrahimpour (Journal of Hyperstructures, 2017)
Let n ≥ 2 be a positive integer, R be a commutative ring with identity and M be a unitary R-module . In this paper we study the (n − 1, n)-weakly prime submodules of direct product of modules. Also, we show that for some special cases, every proper submodule is (n − 1, n)-weakly prime.